Design of Assessment Instrument for Mathematical Critical Thinking Indicators-Based Essay Questions for Vocational and High School Students Using the Rasch Model - Jarot Rudi Hartato; Nizaruddin Nizaruddin; Lukman Harun (JURNAL PENDIDIKAN MATEMATIKA, 2025)
This research aims to create a measurement tool for Critical Thinking Skills (CTS) in mathematics. The instrument was analysed using the Rasch model. The analysis was conducted to determine the results of the content validity test (item suitability), reliability test, dimensionality test (construct validity), person separation test, and item separation, and to analyse the items' difficulty level. This research uses the R&D model with the 4D model. Data collection methods through interviews with two teachers, literature studies to determine CTS indicators, questionnaire validation of CTS test instruments, and CTS test questions given to students. The sampling technique used was saturated sampling. The indicators of CTS are Interpretation, analysis, evaluation, and inference. The results for each instrument item are valid; construct validity is good, reliability is sufficient, and Cronbach's alpha is 0.68. The results of the person separation analysis show that students are divided into two groups, and item separation shows that the questions are divided into five groups. The measure (logit value) analysis results show that the interpretation indicator question is easy, the analysis indicator question is very difficult, the evaluation indicator question is moderate, and the inference indicator question is difficult. This research fills the literature gap by developing CTS indicator-based instruments validated by the RASCH approach, which has not been widely applied in SMA / SMK. Keywords: Critical Thinking, Test Instrument, Rasch Model